Strategic Options in Fair Trade Retailing - Nicholls, A (2002)
Notes that there has been a significant increase in the market for fair trade products in the UK over the past five years. Provides a definition of fair trade and goes on to set a context for the expansion of this market by examining the key drivers behind it, particularly noting the growth of ethical consumerism as a contributory factor. Develops the ethical strategy matrix, outlining the strategic options open to retailers for addressing this increase in ethical consumerism. It is argued that addressing the fair trade market in the UK offers retailers not only the opportunity to develop their profile in terms of corporate social responsibility, but also a chance to develop a competitive advantage in a new niche market. Recasts Strong’s marketing analysis of the difficulties of translating fair trade principles into actual purchase behaviour into an operational context and proposes solutions to the issues raised.